Improvement of IDWG Related to Hypotension Events in Hemodialysis Patients - Fery Juliardi; Febriantoni Febriantoni; Juliana Dewi; Muhammad Aryandra Hasibuan; Tiarnida Tiarnida; Katiti Katiti (Jurnal Penelitian Perawat Profesional, 2020)
Hemodialysis which is one of the treatments performed on patients with kidney failure has been done with the help of 15% / minute / 1.73. While hemodialysis is safe and beneficial for patients, it does not mean that it has no side effects, one of which is an increase in IDWG. Increase in body weight between IDWG hemodialysis or Interdialytic Weight Gain has side effects that often occur as well, one of which occurs intradialisis hypotension. The study aims to determine the relationship of increased IDWG with the incidence of hypotension in hemodialysis patients at the Rasyida Kidney Hospital in Medan. Quantitative research design with analytic surveys conducted through cross sectional research. The population in this study were chronic kidney failure patients who performed hemodialysis at the Rasyida Kidney Hospital in Medan, with a total of 380, with a sample of 22 respondents using purposive sampling. The majority of hemodialysis patients in Medan Rasyida Kidney Special Hospital approve> 50 years (50%), and 50% are male and 50% female, 50% of patients can be hypotensive and increase IDWG. Chi square test results obtained p-value of 0,000. So, it can be concluded that there is a relationship between an increase in IDWG and the incidence of hypotension in hemodialysis patients.